Pengaruh Pendekatan Saintifik terhadap Motivasi dan Hasil Belajar Biologi Siswa - Diah Dwi Mayasari; Yunita Wardianti; Yuli Febrianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the effect of the scientific approach to the motivation and learning outcomes of biology class X students of SMA Negeri 6 Model Lubuklinggau. The research method used is quantitative research with pure experimental research using pre-test and post-test group design. The population in this study were all students of class X MIPA, amounting to 88 students. Samples were taken randomly so that there were 30 students in Class X MIPA 1 as an experimental class and 27 students in Class MIPA 2 as a control class, data collection was done by using test and questionnaire techniques. The results of the study, it is known that the tcount for motivation obtained 6.631 results> ttable = 1.671, with a significant level α = 0.05 and dk 55. Data collected for the analysis of learning outcomes with a significant level α = 0.05 and dk 55, note the tcount = 11.23 > table = 1.671. There are significant differences in motivation scores and student learning outcomes before and after learning interventions are used using a scientific approach. In conclusion, the scientific approach in learning biology has a significant influence on the motivation and learning outcomes Keywords: learning outcomes, motivation, scientific approach.